A companion to Luis de Molina - Kaufmann, Matthias; Aichele, Alexander (Brill's companions to the Christian tradition, 2014)
Focused on Molina's main works the book offers the first comprehensive synopsis of his partly revolutionary philosophical positions concerning metaphysics of freedom, political philosophy, theory of law and their historical and systematic influence from the 17th century until today. Since his rediscovery by Alwin Plantinga in the 1970s Molinism concerning the possibility of counterfactuals of freedom is one of the main issues of contemporary analytic philosophy of religion. Albeit that fact, Luis de Molina (1535-1600) still remains one of most influential and most unknown authors of late scholasticism and early modern philosophy. The papers collected in this volume treat the whole range of issues posed by his metaphysics as they are exposed in his revolutionary "Concordia" and by his practical philosophy esp. of law and economics in his groundbreaking work on 'De Justitia et Jure' as well as Molina's historical commitments and his influences on philosophy. So, the Companion offers the first comprehensive and thorough overview of Molina's thought